Understanding of information retrieval systems : management, types, and standards - Bates, Marcia J. (CRC Press, 2012)
"Information retrieval (IR) is the area of study concerned with searching for documents, information within documents, and metadata about documents, as well as searching relational databases and the World Wide Web. This book covers the management, types, and technical standards of these increasingly important systems. It discusses all types of information retrieval systems, including those used in medicine, geographic information, and music, as well as retrieval in computer-supported collaborative work, Web mining, social mining, and the Semantic Web. Library and museum IR systems are also covered. Leading contributors in the field address digital asset management, piracy in digital media, records compliance, information storage technologies, and data transmission protocols"-- Provided by publisher